Identification of Cuproptosis-Related Genes in Nonalcoholic Fatty Liver Disease. (21st February 2023) - Wu, Chutian; Liu, Xiongxiu; Zhong, Lixian; Zhou, Yun; Long, Linjing; Yi, Tingzhuang; Chen, Sisi; Li, Yuting; Chen, Yanfang; Shen, Lianli; Zeng, Qiuting; Tang, Shaohui
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most prevalent hepatic pathology worldwide. However, the precise molecular mechanisms for NAFLD are still not sufficiently explained. Recently, a new mode of cell death (cuproptosis) is found. However, the relationship between NAFLD and cuproptosis remains unclear. We analyzed three public datasets (GSE89632, GSE130970, and GSE135251) to identify cuproptosis-related genes stably expressed in NAFLD. Then, we performed a series of bioinformatics analyses to explore the relationship between NAFLD and cuproptosis-related genes. Finally, 6 high-fat diet- (HFD-) induced NAFLD C57BL/6J mouse models were established to carry out transcriptome analysis. The results of gene set variation analysis (GSVA) revealed that the cuproptosis pathway was abnormally activated to a certain degree (p = 0.035 in GSE89632, p = 0.016 in GSE130970, p = 0.22 in GSE135251), and the principal component analysis (PCA) of the cuproptosis-related genes showed that the NAFLD group separated from the control group, with the first two principal components accounting for 58.63%-74.88% of the variation. Among three datasets, two cuproptosis-related genes ( DLD and PDHB, p < 0.01 or 0.001) were stably upregulated in NAFLD. Additionally, both DLD (AUC = 0.786 – 0.856 ) and PDHB (AUC = 0.771 – 0.836 ) had favorable diagnostic properties, and the multivariate logistics regression model further improved the diagnostic properties (AUC = 0.839 – 0.889 ). NADH, flavin adenine dinucleotide, and glycine targeted DLD, and pyruvic acid and NADH targeted PDHB in the DrugBank database. The DLD and PDHB were also associated with clinical pathology, especially with steatosis ( DLD, p = 0.0013 – 0.025 ; PDHB, p = 0.002 – 0.0026 ) and NAFLD activity score ( DLD, p = 0.004 – 0.02 ; PDHB, p = 0.003 – 0.031 ). What is more, DLD and PDHB were correlated with stromal score ( DLD, R = 0.38, p < 0.001 ; PDHB, R = 0.31, p < 0.001 ) and immune score ( DLD, R = 0.26, p < 0.001 ; PDHB, R = 0.27, p < 0.001 ) in NAFLD. Furthermore, Dld and Pdhb were also significantly upregulated in the NAFLD mouse model. In conclusion, cuproptosis pathways, especially DLD and PDHB, could be potential candidate genes for NAFLD diagnostic and therapeutic options.